The girl he used to know [compact disc, unabridged] - Garvis Graves, Tracey (Macmillan Audio, 2019)
A tumultuous but tender love affair between a socially awkward chess club member and a courageous, quirky girl is shattered by an unforeseen tragedy that forces them to confront their anxieties when they reunite a decade later.